Editing Modernity : Women and Little-Magazine Cultures in Canada, 1916-1956 - Irvine, Dean J. (Dean Jay) (Book collections on Project MUSE., 2008)
The period between 1916 and 1956 was a unique interval in the history of Canadian publishing. During this period not only were a significant number of non-commercial literary, arts, and cultural magazines established, but it also happened that an unprecedented number of those involved in the creation and subsequent editing of this new type of magazine - the little magazine - were women. Based on extensive new archival and literary historical research, Editing Modernity examines these Canadian women writers and editors and their role in the production and dissemination of modernist and leftist little magazines.At once a history of literary women and of the emergent formations and conditions of cultural modernity in Canada, Irvine's study relates women's editorial work and poetry to a series of crises and transitions in modernist and leftist magazine communities, to the public hearings and published findings of the Massey Commission of 1949-51, and to the later development of feminist literary magazines and editorial collectives during the 1970s and 1980s. Writers and editors examined in this study include Dorothy Livesay, Anne Marriott, Floris McLaren, P.K. Page, Miriam Waddington, Flora Macdonald Denison, Florence Custance, Catherine Harmon, Aileen Collins, and Margaret Fairley.